Effect of Frying Process on Nutritional Property, Physicochemical Quality, and in vitro Digestibility of Commercial Instant Noodles - Wang, Jin; Li, Ang; Hu, Jiaqiang; Zhang, Bowei; Liu, Jingmin; Zhang, Yan; Wang, Shuo (Frontiers in Nutrition, 2022)
The effects of frying process on nutritional property, physicochemical quality, and in vitro digestibility of instant noodle products were investigated in the present study. Scanning electron microscope (SEM) and Fourier transform infrared spectrometer (FT-IR) were also used to explore the changes in microstructure and protein transformation. Noodles after frying process showed lower proportion of carbohydrate, protein, fiber, as well as total starch and digestible starch, but higher content of fat and resistant starch in the proximate analysis. Frying process was also considered to improve the texture, surface color, and sensory properties of instant noodle products, accompanied with better cooking quality including shorter cooking time and lower cooking loss during the rehydration. The honeycomb-like, porous, and less uniformed structure as well as the higher levels of β-turns and β-turns, and the lower proportion of α-helixes of protein structure from fried instant noodle were also observed. The in vitro digestibility of starch and protein were downregulated in the fried group (81.96% and 81.31, respectively, on average) compared with nonfried group (97.58% and 88.78, respectively, on average). Thus, frying process lowered the glycemic index and regulated protein secondary structure by inhibiting continuous digesting enzyme activity, generating starch-lipid complexes, and changing the levels of protein transformation. In conclusion, our findings will provide an innovative evaluation of frying process on instant noodles and even other various starch-based prepared food products.